A numerical analysis for energy savings of different oriented and insulated walls in the cold climate of Turkey - Simulation-based study - Aksoy, U. Teoman (Elsevier Science Sa, 2012)
Most of the energy expended in buildings is used for heating. Heating insulation of walls has been gaining much more interest in recent years not only because of the hazardous effects energy consumption on the environment, but also the high costs of energy sources. Therefore, the relationship between insulation thickness and orientation was investigated in this paper for in Elazig (38.4 degrees N), one of the cold regions in Turkey. One dimensional transient heat transfer problem of the walls with and without insulation was solved by using the explicit finite difference method. In the illustration model, hourly values of heat losses of mass and walls were calculated. The annual energy cost was calculated for walls. It was observed that energy consumption will decrease by 19-78%, depending on the insulation thickness. Payback periods based on insulation cost are 1.69-2.89 years. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Energy saving; Climatic comfort; Payback period; Energy cost; Insulation thickness